A multi-spark electrohydraulic shock wave generator with adjustable pressure field distribution and beam steering capability - Sankin, Georgy N.; Fang, Zheng; Gu, Juanjuan; Jing, Yun; Zhong, Pei (Frontiers in Urology, 2023)
Background and Objective: Contemporary shock wave lithotripters produce axisymmetric pressure fields, which cannot account for the variations in kidney anatomy and the effect of respiratory motion of the patient during lithotripsy. To overcome this limitation, we have developed a new shock wave source with flexible control of the firing patterns from multiple sparks, leading to the creation of non-axisymmetric pressure fields with adjustable beam size and shape. Materials and Method: Ninety electrohydraulic transducers are uniformly distributed on a spherical basin, arranged in 5 concentric rings and sub-divided into 6 sectors. Each transducer is 3D-printed and comprised of 45 titanium microelectrodes of 300 m in tip diameter embedded in epoxy. Different combinations of the transducers can be energized by two high-voltage pulse generators to alter the pressure field, which are characterized by hydrophone measurement. Results: The pressure field produced by the new shock wave source at 19 kV can be either axisymmetric with a circular (-6 dB) focal plan of 14.8 mm in diameter, or non-axisymmetric with an elliptical (-6 dB) focal plan with a long axis of 22.7 mm and a short axis of 15.1 mm. The elongated beam generates a peak pressure (p+) of 33.7±4.1 MPa and a stone comminution (SC) of 42.2±3.5% after 150 pulses, compared to p+ = 36.2±0.7 MPa and SC = 28.6 ± 6.1% by the axisymmetric beam. The difference in comminution efficiency produced by the two pressure fields is statistically significant (p < 0.05). Conclusion: We have developed a multi-spark shock wave generator capable of flexibly adjusting the shape and size of the focal pressure field. This unique feature may help to improve the efficiency of stone comminution in kidneys of different anatomic features, and potentially lower the of shock wave-induced tissue injury during lithotripsy procedures.